The logics of globalization : studies in international communication - Kavoori, Anandam P. (Lexington Books, 2009)
"This book presents the theoretical language and methodological tools needed for thinking through issues of global media representation. It brings students into a conversation about global culture and communication through the presentation of a conceptual language to discuss the "logics of globalization" (i.e., nationalism, modernism, postmodernism/colonialism, capitalism, and terrorism). Anandam Kavoori uses this language to critically interrogate various media texts."--Jacket